Comparison of Sonication with Maceration on Antioxidant Potency of Anthocyanin and Karotenoid of Tamarillo (Solanum betaceaum Cav.) - Gusti Ayu Kadek Diah Puspawati; Yustinus Marsono; Supriyadi Supriyadi; Ria Armunanto (agriTECH, 2018)
Tamarillo is an underutilized fruit in Indonesia, despite the fact that it contains two pigments (anthocyanin and carotenoid) with different properties (polar and non polar). Besides, there is a scarce information about extraction of anthocyanin and carotenoid of Tamarillo using sonication extraction. This study was aimed to investigate the comparison of extraction methods of sonication with maceration on antioxidant potency of anthocyanin and carotenoid of Tamarillo. Two pigmen types (anthocyanin and carotenoid) were extracted using two different methods (sonication and maceration). The parameters of analysis were yield, antioxidant activity (DPPH) with IC50, Ferric Reducing Antioxidant Power (FRAP), anthocyanin total, carotenoid total, phenolic total and scanning electron microscope of cover cell of material. The antioxidant potencies for both anthocyanin and carotenoid by sonication method were higher than those of obtained by maceration method. The results showed that both sonication and maceration were suitable for extraction of anthocyanin and carotenoid from Tamarillo.